Leveraging Isothermal Titration Calorimetry to Explore Structure–Property Relationships of Protein Immobilization in Metal–Organic Frameworks. (9th August 2022) - Tai, Tzu‐Yi; Sha, Fanrui; Wang, Xiaoliang; Wang, Xingjie; Ma, Kaikai; Kirlikovali, Kent O.; Su, Shengyi; Islamoglu, Timur; Kato, Satoshi; Farha, Omar K.
Abstract: Proteins immobilized in metal–organic frameworks (MOFs) often show extraordinary stability. However, most efforts to immobilize proteins in MOFs have only been exploratory. Herein, we present the first systematic study on the thermodynamics of protein immobilization in MOFs. Using insulin as a probe, we leveraged isothermal titration calorimetry (ITC) to investigate how topology, pore size, and hydrophobicity of MOFs influence immobilization. ITC data obtained from the encapsulation of insulin in a series of Zr‐MOFs reveals that MOFs provide proteins with a hydrophobic stabilizing microenvironment, making the encapsulation entropically driven. In particular, the pyrene‐based NU‐1000 tightly encapsulates insulin in its ideally sized mesopores and stabilizes insulin through π‐π stacking interactions, resulting in the most enthalpically favored encapsulation process among this series. This study reveals critical insights into the structure–property relationships of protein immobilization. Abstract : Isothermal titration calorimetry was leveraged to systematically study how the structural properties of MOFs, such as hydrophobicity, pore size, and topology, influence the thermodynamics of protein immobilization by using a series of Zr‐MOFs as the host and insulin as the model protein probe. The thermodynamics of binding can elucidate a major driving force for protein encapsulation, which could not be revealed in bulk adsorption studies.